2011
DOI: 10.1093/scan/nsr045
|View full text |Cite
|
Sign up to set email alerts
|

An fMRI study of caringvsself-focus during induced compassion and pride

Abstract: This study examined neural activation during the experience of compassion, an emotion that orients people toward vulnerable others and prompts caregiving, and pride, a self-focused emotion that signals individual strength and heightened status. Functional magnetic resonance images (fMRI) were acquired as participants viewed 55 s continuous sequences of slides to induce either compassion or pride, presented in alternation with sequences of neutral slides. Emotion self-report data were collected after each slide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(58 citation statements)
references
References 92 publications
2
53
0
1
Order By: Relevance
“…In addition, studies on false-belief tasks showed a bilateral activation of the inferior frontal gyrus in tasks with high demand on the inhibition of the observer's own perspective (Hartwright et al, 2012;van der Meer et al, 2011). Finally, the inferior frontal gyrus has been involved in emotional empathy (Banissy et al, 2012;Schulte-Rüther et al, 2007;Shamay-Tsoory et al, 2009), cognitive empathy (Hooker et al, 2010) and self-reported feelings of compassion (Simon-Thomas et al, 2012). The results for the supramarginal gyrus and the right inferior frontal cortex once again fit well to ToM findings in the literature.…”
Section: Discussionsupporting
confidence: 84%
“…In addition, studies on false-belief tasks showed a bilateral activation of the inferior frontal gyrus in tasks with high demand on the inhibition of the observer's own perspective (Hartwright et al, 2012;van der Meer et al, 2011). Finally, the inferior frontal gyrus has been involved in emotional empathy (Banissy et al, 2012;Schulte-Rüther et al, 2007;Shamay-Tsoory et al, 2009), cognitive empathy (Hooker et al, 2010) and self-reported feelings of compassion (Simon-Thomas et al, 2012). The results for the supramarginal gyrus and the right inferior frontal cortex once again fit well to ToM findings in the literature.…”
Section: Discussionsupporting
confidence: 84%
“…Our approach is based on a standard definition of compassion as a 'sensitivity to suffering in self and others with a commitment to try to alleviate and prevent it' [21,46,64,104]. The impetus for this research was inspired by a wealth of research showing e that developing caring and compassion-focused motives for self and others has a range of benefits: on genetic expression [14,31,109], physiological processes [9,68,71,73,107,108], psychological processes [63,64,66,108], and social relationships [16,18,100]. Cultivating compassion for self and others has also become a central focus for the development of psychotherapies [35,37,40,61,67,69,77,96].…”
Section: Introductionmentioning
confidence: 99%
“…Although scientists and laypeople typically characterize compassion as a positive emotion (Keltner & Lerner, 2010; Shaver, Schwartz, Kirson, & O’Connor, 1987), reports of compassion experiences indicate that compassion can feel unpleasant. Images depicting poverty and vulnerable infants, for example, simultaneously elevated reports of compassion and distress (Simon-Thomas et al, 2012). The valence of compassion appears illusive, but a scientific account depends on a greater understanding of the subjective experience of compassion.…”
mentioning
confidence: 99%